The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.3327/jnst.33.641
|View full text |Cite
|
Sign up to set email alerts
|

The Passivation Effects of Magnesium Ion on PHWR Primary Heat Transfer System Structural Materials.

Abstract: Zinc ion injection passivation technique is being used in BWRs in order to reduce the radiation field build-up around the reactor coolant system. In the case of PWRs and PHWRs, the chemistry of the primary coolant system and the materials of construction are different from those of BWRs. In the present paper, the results of studies on the effect of magnesium ion in modifying the oxide layers formed under PHWR chemistry conditions are reported. The experiments carried out at room temperature and at 265'C are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Thus there is a need for an alternative to Zn, which should have properties similar to zinc but more effective in reducing the radiation field in PHWRs. As zinc and magnesium have similar properties by virtue of their position in the periodic table, it was felt that magnesium can be used as a substitute [3] for zinc ion in reducing the radioactivity build-up. Experiments carried out under simulated PHWR PHT system conditions indicated that the thickness of the oxide formed over carbon steel and Incoloy-800 were low when magnesium was present in the water [3].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus there is a need for an alternative to Zn, which should have properties similar to zinc but more effective in reducing the radiation field in PHWRs. As zinc and magnesium have similar properties by virtue of their position in the periodic table, it was felt that magnesium can be used as a substitute [3] for zinc ion in reducing the radioactivity build-up. Experiments carried out under simulated PHWR PHT system conditions indicated that the thickness of the oxide formed over carbon steel and Incoloy-800 were low when magnesium was present in the water [3].…”
Section: Introductionmentioning
confidence: 98%
“…As zinc and magnesium have similar properties by virtue of their position in the periodic table, it was felt that magnesium can be used as a substitute [3] for zinc ion in reducing the radioactivity build-up. Experiments carried out under simulated PHWR PHT system conditions indicated that the thickness of the oxide formed over carbon steel and Incoloy-800 were low when magnesium was present in the water [3]. Also, in both alloys significant concentration of magnesium could be detected using X-ray photoelectron spectroscopic technique.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In order to determine the functional surface active sites type, XPS was first employed to identify the chemical states of related surface metals before and after reaction [Velmurugan et al, 1996]. As can be seen in Fig.…”
Section: Results Inmentioning
confidence: 99%
“…Depending on the type of reactor, either an oxidising formulation followed by a reducing formulation or only the latter is used for the purpose. [2][3][4] Permanganate based oxidising reagents such as alkaline permanganate, 5 nitric acid permanganate 5 and permanganic acid 6 are generally used for the pretreatment in the decontamination process to dissolve chromium from the iron, chromium and nickel containing oxide films formed on stainless steel and other chromium containing alloys. 7 During such process, the core material, which is zircaloy-2, will also come in contact with the decontamination solution.…”
Section: Introductionmentioning
confidence: 99%